Le cheval et son cavalier dans la peinture murale des XIe-XIIIe siècles - Christian Davy (In Situ)
The horse is an animal met in a sufficiently regular way in the mural painting of the 11th – 13th centuries in France to collect to a certain extent invaluable information on its state and the hardware requirement with its ride. The representations of the horse and its rider are not only one reflection, even mirror, of the feudal society, but also a tool of raising the moral standard.